Epigenetic regulation in plant abiotic stress responses - Chang, Ya‐Nan; Zhu, Chen; Jiang, Jing; Zhang, Huiming; Zhu, Jian‐Kang; Duan, Cheng‐Guo (Journal of integrative plant biology, 2020)
In eukaryotic cells, gene expression is greatly influenced by the dynamic chromatin environment. Epigenetic mechanisms, including covalent modifications to DNA and histone tails and the accessibility of chromatin, create various chromatin states for stress‐responsive gene expression that is important for adaptation to harsh environmental conditions. Recent studies have revealed that many epigenetic factors participate in abiotic stress responses, and various chromatin modifications are changed when plants are exposed to stressful environments. In this review, we summarize recent progress on the cross‐talk between abiotic stress response pathways and epigenetic regulatory pathways in plants. Our review focuses on epigenetic regulation of plant responses to extreme temperatures, drought, salinity, the stress hormone abscisic acid, nutrient limitations and ultraviolet stress, and on epigenetic mechanisms of stress memory. Epigenetic mechanisms create various chromatin states for gene expression that is important for adaptation to harsh environmental conditions. Recent studies have revealed important involvements of epigenetic mechanisms in plant abiotic stress responses. This review summarizes recent progress on the cross‐talk between abiotic stress responses and epigenetic regulatory pathways in plants.